Covariation analysis of the master bacterial DNA replication initiator DnaA. Issue 5 (27th May 2022) - Dobby, Laura; Murray, Heath
Abstract : Bacterial DNA replication initiation is governed by DnaA: an oligomeric protein belonging to the ATPases associated with diverse cellular activities (AAA+) superfamily. The master replication initiator is present in all known bacterial pathogens; thus, it is an attractive target for drug discovery. Here, an in-silico evolutionary covariation analysis of DnaA amino acid residues was conducted using EVcouplings, a Python framework, to investigate connections between key protein residues. Several co-evolving amino acid pairs were identified and characterized using PyMol to visualize the residues on DnaA crystal structures. I hypothesize that some co-evolving pairs, particularly those spatially connected, are likely important for structural integrity of the protein. Interestingly, one co-evolving pair of residues (A. aeolicus Val121 and Ser229) was found to be separated by 27 angstroms, suggesting a more complex relationship connects these two sites. Thus, analysing co-evolution of DnaA residues supports known structural information and may predict either allosteric connections within DnaA or contacts between DnaA and other binding partners.